Teacher’s Affective Support and Its Influence Toward Students’ Academic Effort and Academic Performance: A Structural Equation Model Approach - Magana, Gilbert S. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Effective teaching requires connecting with students and addressing their emotional needs. This study examines the relationships among academic performance, effort, self-efficacy, enjoyment, hopelessness, and teachers' affective support in mathematics education. Using PLS-SEM with WarpPLS 7.0, data from 261 Bongabon Senior High School learners were analyzed. Results show that lower-performing students may exert more effort to improve, as academic performance negatively influences effort. Teachers' affective support enhances self-efficacy and belonging but negatively impacts performance. Enjoyment significantly influences effort, self-efficacy, and hopelessness but not performance. Belonging improves self-efficacy and enjoyment but does not affect hopelessness. Findings highlight emotional support's role in fostering self-efficacy and enjoyment, recommending further exploration of mediators and strategies to enhance student achievement.